Strategi Dinas Pemberdayaan Perempuan Perlindungan Anak Dan Pemberdayaan Masyarakat Dalam Mengurangi Tindak Kekerasan Pada Perempuan Di Kota Tanjungpinang (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
The background of this research is in Tanjungpinang Mayor Regulation Number 34 of 2016 concerning implementing government affairs in the field of gender mainstreaming, protection of women and partnerships, child protection and community empowerment. The purpose of this study was to find out the strategy of the Office of Women's Empowerment, Child Protection and Community Empowerment in Tanjungpinang City in reducing acts of violence against women. The methodology used in this study is descriptive qualitative with primary and secondary data sources. The analysis technique is carried out through the process of data reduction, data presentation, and drawing conclusions. This type is able to describe in more depth how the strategy is structured, implemented, and expanded. research results based on indicators (1) Having goals which include reducing violence, protecting victims and completely protecting women and children from acts of violence. (2) creating a safe and supportive environment. (3) carrying out directives from the government and requiring society as a whole, the flow of reports of acts of violence, up to punishment for the perpetrators of violence. (4) strong action against violence against women and DP3APM's commitment to conducting outreach to change people's mindset, behavior and cultural changes regarding acts of violence. (5) Continuous learning is very important in reducing cases of violence against women, making a schedule of activities and evaluating programs carried out with the aim of knowing the extent to which success has been achieved. the conclusion of this study concludes that the DP3APM strategy has been effective but has not been carried out thoroughly. The suggestion from this research is that DP3APM involves the community more in participating in these outreach activities.